1995
DOI: 10.1007/bf01712336
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lithium reabsorption from lithium-chloride-coated heat and moisture exchangers

Abstract: LiCl coat enhances HMEs' performance greatly, but reabsorption and systemic action must be considered. In adults, serum lithium levels were lower than the therapeutic range, but lithium is effective at low concentrations and it has a narrow therapeutic range; moreover, toxicity can be observed within this range too. In children, the risk of toxicity is much greater. When lithium coated HMEs are used, the risk/benefit ratio between good performance and systemic reabsorption must be evaluated carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…One study has shown that lithium can be absorbed into the body in toxic amounts. This may present a greater risk to small children (30). The HCHF adds a bacterial filter between the insert and the source of inspired gas.…”
Section: Humidification Backgroundmentioning
confidence: 99%
“…One study has shown that lithium can be absorbed into the body in toxic amounts. This may present a greater risk to small children (30). The HCHF adds a bacterial filter between the insert and the source of inspired gas.…”
Section: Humidification Backgroundmentioning
confidence: 99%
“…These include an increase in the work of breathing, 5 airway obstruction [6][7][8] and lithium toxicity. 9 Airway obstruction develops when moisture, typically patient secretions, nebulized drugs 10 or moisture from within the circle circuit, occludes the pores within the HMEF, leading to a significant increase in resistance. Fortunately, moisture levels typically seen in routine use do not result in obstruction.…”
mentioning
confidence: 99%
“…A tolerabilidade é um aspecto especialmente preocupante, pois as crianças são mais susceptíveis aos efeitos colaterais que adultos (Rosi et al, 1995, Campbell et al, 1991. Dessa forma, entende-se a obtenção de valor máximo dos exames de litemia menor em crianças que adolescentes, demonstrando esse cuidado no limite da faixa terapêutica utilizada para as crianças (Tabela 10: valor máximo em crianças = 1,1 mEq/L, e valor máximo em adolescentes = 1,5 mEq/L).…”
Section: Ii5 Discussãounclassified